2009
DOI: 10.1007/s10157-009-0252-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive encephalopathy in patients with chronic renal failure caused by stopping antihypertensive agents: a report of two cases

Abstract: We herein report two cases of patients with chronic kidney disease who developed hypertensive encephalopathy, which occurred after a sudden discontinuance of antihypertensive agents. Both patients underwent care at our hospital after experiencing neurological abnormalities. In both patients, magnetic resonance imaging (MRI) revealed edema in the cerebral white matter and cortices, basal ganglia, brainstem, and cerebellum. Though recently the number of reports about hypertensive encephalopathy has decreased, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…PRES has also been reported in patients with chronic renal failure undergoing peritoneal dialysis (14,15), after blood transfusions (16), or following the discontinuation of antihypertensive agents (17). At the initiation of hemodialysis, a case of PRES associated with dialysis disequilibrium syndrome was also previously reported (18).…”
Section: Discussionmentioning
confidence: 90%
“…PRES has also been reported in patients with chronic renal failure undergoing peritoneal dialysis (14,15), after blood transfusions (16), or following the discontinuation of antihypertensive agents (17). At the initiation of hemodialysis, a case of PRES associated with dialysis disequilibrium syndrome was also previously reported (18).…”
Section: Discussionmentioning
confidence: 90%
“…But in 2009, Decker et al demonstrated their biopsy studies that RPLS and HE have a common pathologic base. The further support was added that RPLE and HE are similar, even if not the same disease [17] .…”
Section: Discussionmentioning
confidence: 97%
“…Currently, there are three main hypotheses (7,15,21): i) The cerebral hyperperfusion theory, stating that blood pressure rises so highly and rapidly that it goes exceeds the upper limit of cerebrovascular autoregulation. This dysfunction stimulates small arteries to undergo expansion rather than contraction and leads to cerebral hyperperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of PRES is not fully understood and there are a number of hypotheses regarding its mechanism of action (5). Previous studies have demonstrated that PRES is associated with different clinical syndromes (6)(7)(8)(9)(10) including acute hypertension, preeclampsia/eclampsia, antineutrophil cytoplasmic autoantibody-associated vasculitis,…”
Section: Introductionmentioning
confidence: 99%